Grey Based Taguchi Optimization Method for Abrasive Wear Appraisal of Fibre-Reinforced PTFE Composites - Ibrahim , Musa Alhaji; Yusuf, Auwalu Gidado; Dambatta, Murtala Sule; Kunya, Bashir Isyaku; Tambaya, Magaji; Alhassan, Yusuf (International Journal of Integrated Engineering, 2023)
The current study is aimed at optimizing the abrasive wear property of fibre reinforced polytetraflouroethylene (PTFE) composites. The test was contrived based on Taguchi L9 orthogonal array for the optimization of test trials. To appraise the abrasive wear trend of the PTFE based composites satisfying multi-objective criteria, Taguchi method combined with grey relational analysis (GRA) has been used. Abrasive wear test was performed using pin-on-disc configuration as per ASTM G99 standard involving four process parameters. Analysis of variance was used to establish significant parameters which influence the abrasive wear of PTFE composites. Observation revealed that grit size has the most significant effect on abrasive wear of reinforced PTFE composites. After exhaustive investigation of parameters, optimum combination of parameters was established. Linear regression model was built to predict the optimized conditions. The model as well as the optimum parameter values could be used by the abrasion industries for reduction in the time and cost expanded on wear test thus increasing productivity.